Physical Therapy for Neurological Conditions in Geriatric Populations - Carmeli, Eli (Frontiers in Public Health, 2017)
With increased age, patients often face age-related neurology diseases that can affect level of function and well-being. Despite neuro-physiological changes affecting the brain function and stracture, the aged brain, in some degree, can learn and relearn due to phenomenon known as ‘Neuroplasticity’. Physical Therapy (PT) of the elderly patient with a neurologic disease focuses in particular on sensory-motor impairments, postural control coordination and prevention of sarcopenia. PT for neurologic patients has a strong influence on their quality of life, ability to live independently and life expectancy. However, in many developed and developing countries the profession of PT is underfunded and understaffed. This paper provides a brief overview on a) age related disease of central nervous system, b) the principles, approaches and doctrines of motor skill learning and point out the most common treatment models that PTs use for neurological patients.